PERANCANGAN PERBAIKAN KOMUNIKASI PEMASARAN FORTUNA TENUN IKAT BALI MENGGUNAKAN METODE BENCHMARKING DAN ANALYTICAL HIERARCHY PROCESS - Pramesti, Ni Nyoman Putri Ayu; Amani, Husni; Kusumayanti, Ima Normalia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Fortuna is one of the MSMEs that is engaged in fashion by producing and selling Balinese Weaving Fabric (Tenun Ikat Bali) . Creating awareness and knowledge about products can be done through marketing communications. Fortuna has implemented six marketing communication mixes from the eight existing communication mixes but it has not been implemented optimally. This research aims to design marketing communication programs using the benchmarking method and the Analytical Hierarchy Process (AHP) tool to determine the selected benchmark partner. The benchmarking method was used to determine the gap between Fortuna's marketing communication program and selected benchmark partners as a reference in designing recommendations for improvement in the marketing communication program. This research formulates 16 needs attributes, which used as a reference to develop recommendations  for Fortuna’s marketing communication programs in each marketing communication mix.